Colombia. The construction of a narrative of historical memory as a political process (2020)
The objective of this article is to deal with memory in Colombia from the point of view of political discourse and public policies. This dual approach supposes the facing of the paradoxical construction of a narrative about the war, in a country where, until relatively recently, the existence of an armed conflict was denied, even more so, where there is no consensus regarding the nomenclature of the multiple violent processes that have been suffered through history. An analysis of the social construction of the memory processes is approached in order to compare them with political discourses and with the recent articulation in public policies of the present post-conflict process.